SPIRITUALITIES, RELIGIONS AND THEOLOGIES: POSSIBILITIES IN HEALTH PROMOTION? - Cordeiro de Souza, Anselmo; dos Santos Silva, Wellington; Farias de Oliveira, Elenilda; Tavares Martins, Leonardo (Práxis Teológica, 2021)
Context: The theme of health promotion emerges from public health and is based as a space for reflection and health practice, indicating, among other principles, intersectoral initiatives including three recurrent themes in contemporaneity, namely: spiritualities, theologies and religions. Objectives: To point out brief introductory notes on heuristic aspects of theology, spirituality and religion and possible links and approaches to health promotion, in the perspective that it can be given as a contribution to the panorama of interfaces in the aforementioned themes. Material and methods: This was a theoretical essay that, from the scientific and academic space, taking as a strategy the bibliographic narrative, intended a critical and applied reflection in a theoretical-descriptive approach in two thematic axes: a) epistemological heuristic context; and b) approximations and entanglements. Results: Notwithstanding the ontological, heuristic and epistemic peculiarities among the themes addressed, promising interdisciplinary and intersectorial approaches are outlined in the academic, scientific and professional scope. A panorama of complex and potentially positive relationships is drawn up, with even moderate contributions, with initiatives with both theoretical and practical emphasis, opening up an extensive agenda to be undertaken on the horizon. Conclusions: The role of spirituality, theology and religion in health promotion has already been evidenced by initiatives and collaborations that are still discrete, and even potential, with a theoretical-practical agenda open to construction.